Computer automation and software upgrade of gas sensor characterization system - Chua, Angus Ee Tark. (2009)
The Gas Sensor Characterization System (GSCS) is a computer based program that is designed to acquire and log data readings from the sensors being tested in order to study sensor behaviours and properties under the influence of different experimental conditions.